EDUKASI MEDIA PEMBELAJARAN BERBASIS APLIKASI DI SMK NEGERI 48 JAKARTA - Muhammad Alfadh Jiyad; Reisha Febriliana Hapsari; Putri Utami Ramadhan; Nur Amalia; Hermina Manihuruk; Sunardin Sunardin; Andreas Bramantyo (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The lack of visual and interactive learning resources in the Visual Communication Design (DKV) program presents challenges for students at SMK Negeri 48 Jakarta in understanding Digital Marketing material. This program aimed to enhance students' understanding and engagement through an interactive learning application on the